Get to Know the Financial Institution Pension Fund Program (DPLK) - MARYONO, Maryono; BAGANA, Batara Daniel; SANTOSA, Agus Budi; WIDIATMOKO, Jakobus (Indonesia Strategic Sustainability, 2024)
In general, humans hope for a prosperous life once they reach old age, but in reality, there are still many people whose old age could be more prosperous because they need income that can be used to meet their living needs. The bank pension fund (DPLK) pension program is a choice for planning retirement. Implementation of community service is carried out alternately with 3 or 4 participants per session. This is because the operational activities of PT Mitra Migas Sejahtera Semarang, which operates in Public Fuel Filling Stations (SPBU), must continue to run. Lack of socialization of financial institution pension fund pension programs by organizers, namely banks and insurance, so promotion needs to be increased so that the public can get information about financial institution pension fund pension programs. Only a few people have participated in this pension program, so promotion is needed to increase the number of participants in bank pension fund pension programs.